The Poetry of Hart Crane - Lewis, R. W. B. (Richard Warrington Baldwin) (Book collections on Project MUSE., 1967)
One of the leading critics of our time, R.W.B. Lewis, charts the career of Hart Crane's imagination-of his vision, his rhetoric, and his craft. Crane, who has heretofore been assigned a relatively minor place in American letters, emerges from this rich, dense book as one of the finest poets in our language. Mr. Lewis traces the development of the theme which runs through all of Crane's poetry-the need for the visionary and loving transfiguration of the actual world-and claims that it is this theme which gives Crane's poetry its extraordinary consistency. Mr. Lewis also relates Crane's development as poet to the Anglo-American Romantic tradition and argues that Blake, Wordsworth, Keats, and Emerson are vital to an understanding of Crane's work.Originally published in 1967.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.